Stable production of dissimilar steel joints in construction machinery by narrow gap oscillating laser welding - Yu Fan; Jian Cao; Jun Zhang; Yong zhao; Rongchao Fang; Yeqing Wang; Zheng Chen (Journal of Materials Research and Technology, 2024)
Narrow gap oscillating laser welding with filler wire is a promising technique for joining high-strength steels in construction machinery. In order to investigate the influence of beam oscillation on the surface morphology and microstructure of weld joints of two types of commonly-used high-strength steels, a comparative study between oscillation welding and non-oscillation welding was conducted. High-speed photography technique was employed to reveal the microstructure and mechanical properties of the dissimilar joints. The results showed that laser beam oscillation produces two effects: one was to enlarge the heated surface of molten pool, while the other was to stir the liquid metal in molten pool periodically. Under the first effect, the fusion between sidewall and weld bead layers was promoted, while under the latter, coarse columnar grains ceased to appear, but finer grains were formed. The weld joints between Q355 and 35 steels exhibited excellent tensile impact bending performance, which was attributed to the grain refinement effect. The results also demonstrated that the oscillation welding with a contact angle less than 50° could avoid lack of fusion in multi-pass wire-filling laser welding. The influence of the oscillation welding process on the quality of welding was further discussed.